FRI0052 Higher uric acid is associated with a lower disease activity in rheumatoid arthritis patients. (12th June 2018) - Al-Herz, A.; Aldei, A.; Saleh, K.; Al-Awadhi, A.; Al-Kandari, W.; Hasan, E.; Ghanem, A.; Hussain, M.; Nahar, E.; Abutiban, F.; Alenizi, A.; Ali, Y.; et al.
Abstract : Background: An association between serum uric acid (UA) and disease activity in rheumatoid arthritis (RA) patients has not been well studied. Objectives: We describe RA patients with high and normal UA and study its association with RA activity. Methods: Adult RA patients from The Kuwait Registry for Rheumatic Diseases (KRRD) who satisfied the ACR classification criteria for RA from four major hospitals were studied from February 2013 through April 2017. Patients with recorded UA were identified. Visits with documented UA levels were included. UA of ≥357 µmol/L (6 mg/dL) was considered high. Statistical correlations were made. Results: A total of 564 RA patients with 2710 hospital visits and available UA were identified, 353 (62.6%) females. Mean age 50.8±11.5 years and disease duration 10.5±2.9 years. Mean DAS28 was 2.9±1.2 and mean HAQ-DI 0.77±0.67. Rheumatoid factor (RF) was positive in 431/564 (76.4%) and anti-cyclic citrullinated peptide antibodies (ACPA) in 374/564 (66.3%). Mean UA was 271±78 µmol/L with 12.7% readings being high. There were more males among patients with high UA than with normal UA(56% vs 36%, p<00.1) with no difference in age. UA was negatively correlated with DAS28(p<0.001), CDAI(p<0.001), SDAI(p=0.038), ESR(p=0.034), VAS pain(p=0.049), morning stiffness(p=0.033), patient's global assessment(p=0.006), physician's global assessment(p=0.033), number of tender joints(p<0.001) and number of swollen joints(p<0.001). There was no significant correlation with RF, ACPA or HAQ. The use of steroid, synthetic and biologic antirheumatic drugs, either individually or as a class, was similar among patients with high and normal UA. Conclusions: RA patients with a higher UA had a lower disease activity despite using similar antirheumatic drugs. Reasons behind such association need to be further studied. Disclosure of Interest: None declared